PENGARUH KEPUASAN PEMBAYARAN, KOMITMEN PROFESIONAL, DAN KOMITMEN ORGANISASI PADA PENGAMBILAN KEPUTUSAN ETIS KONSULTAN PAJAK DI PROVINSI BALI - Putu Juna Sutrianta; Sang Ayu Putu Arie Indraswarawati; Anak Agung Ketut Agus Suardika (Hita Akuntansi dan Keuangan, 2020)
Professionals in accounting are professions full of ethical decisions, especially in the profession of Tax Consultants. This study aims to determine the effect of payment satisfaction, professional commitment, and organizational commitment on ethical decision making of Tax Consultants in Bali Province. The population in this study were all Tax Consultants in Bali1 Province, while 155 people were selected as research objects (samples). The sampling technique uses a purposive sampling method. Data were tested using validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple regression analysis, hypothesis test and coefficient of determination. The results showed that the variables of payment satisfaction, professional commitment, and organizational commitment were both positive impact and significant influences on ethical decision making of the Tax Consultant in Bali Province.